Desain Kawasan Wisata Tanggap Pandemi Melalui Pendekatan Klimatis di Puncak Gadhung Mlaten, Desa Caturharjo, Kecamatan Pandak, Kabupaten Bantul - Seputra, Jackobus Ade Prasetya; Mahendarto, Trias (Jurnal Riset Daerah, 2021)
"Pengabdian pada Masyarakat" (Community Service) at Puncak Gadhung Mlaten, Caturharjo Village, Pandak, Bantul, Yogyakarta is conducted as an endeavor to mitigate the impact of COVID-19 pandemic. This program is commenced in August 2020 when Indonesian tourism was in hiatus due to domestic travel restrictions and public hesitations to undergo outdoor activities. As a response, local authorities of Caturharjo Village introduce the concept of pandemic responsive tourism to recover public confidence of traveling outside and be able to visit their village. This attempt is intended to reduce unemployment rate and increase residents' welfare. This service is directed in four steps, there are (1) problem identification and definition, (2) literature study of pandemic responsive design from climate perspective, (3) implementation of climatic findings using ENVI-met v4 as problem solver, and (4) formulating pandemic responsive tourism area. The output of this process is design of Puncak Gadhung Mlaten Tourism Area, Caturharjo Village, Pandak, Bantul, Yogyakarta by fulfilling pandemic responsive and thermal comfort criteria as; air temperature below 28oC, relative humidity between 70-75%, sun hours on public areas above 30 minutes, and wind speed more than 1 m/s.